Performance analysis of government subsidies for photovoltaic industry: Based on spatial econometric model. (March 2021) - Shao, Xuefeng; Fang, Tianshu
Abstract: Energy is the basis for development of material civilization. Since fossil energy can cause environmental problems, clean energy has become the trend of energy development. Solar energy is a kind of resource-rich and clean energy. Therefore, it exists great prospects of development. In addition, the cost of photovoltaic power generation is relatively high, and governmental subsidies are required. In this paper, we propose a spatial econometric model to analyze performance of government subsidies for the photovoltaic industry. When spatial dependence is obvious, classical econometrics begins to fail. At this time, spatial econometrics came into being. This paper evaluates the support policies of photovoltaic industry based on the premise that there is spatial dependence among regions. The results show that the installed capacity of photovoltaics in various regions has begun to show a significant positive correlation since 2012.What's more, the feed-in tariff and R&D subsidy policies have played a positive role in photovoltaic installed capacity from 2012 to 2018. It significantly contributes to the transformation of photovoltaic industry policy. At the same time, this paper expands the application scope of spatial econometric model. Highlights: We apply spatial econometric model to analyze the performance of government subsidies on photovoltaic industry. The installed capacity of photovoltaics has shown a significant spatial agglomeration situation since 2012. The feed-in tariff and R&D subsidy policies play a positive incentive to the photovoltaic installed capacity. The scale of subsidies is in inverse correlation with the distribution of solar energy resources in some regions. We propose countermeasures from the four aspects.